Karakteristik tepung ubi jalar madu (Ipomoea batatas L.) termodifikasi oleh starter mocaf dengan variasi waktu fermentasi - Diniyah, Nurud; Agafatmi, Izzun; Subagio, Achmad; Indarto, Indarto; Irsyam, Mahrus; Aini, Nur; Giyarto, Giyarto (AGROINTEK, 2025)
Honey sweet potato is a potential local tuber from Pasrujambe subdistrict, Lumajang regency to be developed into processed food products. It can be processed into flour to increase the use value of honey sweet potato. The current flour has several shortcomings, including a languid aroma, low water absorption ability, and limited development patterns. Efforts to improve flour characteristics were made by modifying the fermentation method using a mocaf starter. This study aimed to determine the effect of time fermentation on the characteristics of modified honey sweet potato flour and the appropriate of time fermentation to produce the best-modified honey sweet potato flour. The experimental design used was a completely randomized design with one factor, the variation of time fermentation. The variation of fermentation time used was 0, 6, 12, 18, 24, 30, and 36 hours, with 0-hour fermentation as the control with triplicate sample replication. The data were analyzed with ANOVA and further tested with the Duncan Multiple Range Test. The best treatment based on the effectiveness test with a value of 0.54 at 36 hours of fermentation showed a yield value of 21.69%, degree of whiteness of 83.63, pH of 4.11; moisture content of 7.28%; starch content of 49.98%; amylose content of 29.40%; amylopectin content of 20.58%; water holding capacity (WHC) of 252.78%; oil holding capacity (OHC) of 121.94%; swelling power of 13.23 g/g; solubility of 5.52%. The conclusion is that the fermentation time significantly affects the characteristics of modified honey sweet potato flour, and 36 hours of fermentation produces the best-modified honey sweet potato flour.